RARE-26. Evaluating the clinical utility of DNA methylation profiling for choroid plexus tumors. (3rd June 2022) - Macrae, Cassie; Gampel, Bradley; Yeo, Kee Kiat; Lidov, Hart; Chi, Susan; Wright, Karen; Fehnel, Katie; Baird, Lissa; Aldape, Ken; Alexandrescu, Sanda; Clymer, Jessica
Abstract: INTRODUCTION : Choroid plexus tumors (CPT) are rare, potentially aggressive CNS tumors with defined histologic criteria for grading. In recent years, several patients within our practice have demonstrated discordance between histological diagnosis and clinical behavior. DNA methylation profiling has emerged as a potential diagnostic adjunct for aiding clinical planning and treatment approach. In this study, we sought to retrospectively evaluate the clinical utility of DNA methylation profiling within our cohort of patients with CPT. METHODS : We performed a retrospective chart review of all patients with choroid plexus tumors treated at Dana-Farber / Boston's Children's Cancer and Blood Disorder Center between 1990-2021, evaluating the histology, treatment approach, and clinical outcome. Available tissue samples were sent to the National Institute of Health for DNA methylation profiling. RESULTS : Seventeen patients with CPT were identified. Median age at diagnosis was 1.8 years (range: 0.4-27.7). Histologic diagnosis included choroid plexus papilloma (CPP; n=4), atypical choroid plexus papilloma (aCPP; n=5), and choroid plexus carcinoma (CPC, n=8). DNA methylation in an initial subset placed these tumors with the pediatric type A (n=5), pediatric type B (n=6), and adult (n=1) subgroups. For one patient, methylation profiling returned as unclassifiable (possibly representing an alternative diagnosis). Discrepancies with the histologic grade were noted in several cases: one patient diagnosed with CPP grouped with pediatric type B CPT on methylation analysis, had rapid recurrence, and a diagnosis of CPC was made on a re-resection specimen; another patient with aCPP with concerning features was classified as pediatric type A by methylation, and is without evidence of disease after initial complete resection. Survival outcomes based on histologic diagnosis and molecular subgroups are compared and reported. CONCLUSION : DNA methylation profiling is a useful tool for the diagnosis of CPT and may have the potential to guide clinical planning and management.